Fingers Matter: The Development of Strategies for Solving Arithmetic Problems in Children With Apert Syndrome - Hilton, Caroline (Frontiers in Education, 2019)
There is very little research on cognitive outcomes and challenges for children with Apert syndrome. This paper describes the findings of a 2½-year longitudinal exploration of the development of arithmetic skills in 10 children with Apert syndrome, who were aged between 4 and 9 years at the beginning of the study. There is evidence to suggest that children with Apert syndrome underachieve in mathematics, especially in areas requiring competence and confidence arithmetic. This study explored the changing strategies the children used as they developed their arithmetic problem solving skills. Of particular interest were the roles of finger gnosis and finger mobility in supporting the development of these skills. A case study approach was adopted in order to explore the children’s problem solving strategies in depth. Children with Apert syndrome are born with their fingers fused and undergo several operations with the aim of ensuring that they have as many functioning fingers as possible. Finger gnosis and finger mobility were both seen to support arithmetic problem solving strategies and skills and reduce the reliance on mental strategies alone. This study found that children with Apert syndrome are disadvantaged if they are not supported to develop their finger gnosis and finger mobility skills. The findings have implications for children with Apert syndrome, but also add to the literature on the role of finger gnosis and finger mobility in the development of skills in early number and arithmetic.